Notch signaling in diabetic kidney disease: recent progress - Wang, Zhi-Hui; Tu, Wei; Long, Ya-Ni; Li, Peng-Fei; He, Kai-Ying; Wu, Jing (Frontiers in Endocrinology, 2025)
Diabetic kidney disease (DKD) is one of the most serious complications of diabetes mellitus (DM) and the main cause of end-stage renal disease (ESRD). The number of affected patients is increasing annually worldwide. Therefore, it is necessary to establish new strategies to treat DKD and improve prognosis. The Notch signaling pathway is involved in multiple mechanisms in DKD, including glomerular endothelial dysfunction, filtration barrier damage, podocyte EMT and dedifferentiation, tubulointerstitial fibrosis, proximal tubule cell dedifferentiation, macrophage polarization, etc. In addition, Notch signaling interacts with other pathways involved in DKD progression, such as TGF-β, Wnt/β-catenin, mTOR, AMPK, autophagy, etc. Therefore, new ideas for the future treatment of DKD may be provided through clarification of the role of the Notch signaling pathway and development of novel drugs.